Development of Package with the Process of Backward Design Teaching on Interesting Economics for Grade 5 Students at Holy Redeemer Banphai School - Sonsena, Kanticha; Namseethan, Somkhuan; Saengsai, Prayoon (Journal of Graduate MCU KhonKaen Campus, 2024)
This research aimed to 1) develop an effective teaching set using the backward design approach for the topic of “Interesting Economics” for the fifth-year elementary school students at Holy Redeemer Banphai School, Ban Phai District, Khon Kaen Province, to achieve an efficiency of 80/80. 2) Compare the performance before and after learning. 3) Study student satisfaction. The researchers determined the sample group using the Krejcie & Morgan table, with 123 fifth-grade students. The target group was randomly selected, resulting in 32 students from grade 5/4. Research tools included the teaching set using the backward design approach, achievement tests, satisfaction surveys, and a learning management plan using the backward design approach. Data analysis included basic statistics, mean, percentage, standard deviation, and t-test. The research results were as follows: 1. The effectiveness of developing the teaching kit, as measured by the in-class assignment scores, is 86.82/81.43, exceeding the set standard of 80/80 2. The learning achievement scores before and after using the teaching set showed statistically significant improvement at the .01 level, with post-teaching scores higher than pre-teaching scores. 3. Student satisfaction is rated as highly satisfactory ( = 4.65, SD = 0.52)